(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The rapid global proliferation of information technologies has significantly reshaped societal structures, education, and communication. This article explores the potential of media literacy to cultivate moral and ethical worldviews among university students. Drawing from global and national educational paradigms, this study highlights the integral role of media literacy in fostering critical thinking, cultural values, and social responsibility. The findings underscore the necessity of embedding media literacy into educational curricula to support students’ intellectual and moral growth in an era of information abundance